Peran Orang Tua Dalam Pendidikan Karakter Anak Di Rumah Terhadap Perilaku Sosial Di Sekolah - Edelfrida Taek; Intansakti Pius X (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Education is a process of changing a person's behavior through knowledge and life experience that makes him more mature in thought and attitude. Character education is a very important component in building optimal national character. Character building will be effective if done from an early age. Character education is a process of applying moral and religious values to children through science, applying these values to oneself, family, fellow friends, educators and the surrounding environment and God Almighty. In children's character education at home on social behavior at school This research was conducted in an effort to reveal the role of parents in educating children's character whether they have a major contribution in influencing children's social behavior, especially towards children's social behavior in the form of imitation which is the beginning of children's social behavior, children's social behavior towards peers and children's social behavior towards adults around the child. The research method used is the literature study method where the researcher becomes the main instrument in analyzing the books being studied. the importance of the role of parents in instilling discipline in children from an early age so that they are able to develop children's social behavior and the role of the teacher is not only as an educator, but also as an educator of character, morals and culture for students so that a better school atmosphere is created and improves behavior and attitudes between children and each other.